1994
DOI: 10.1161/01.cir.90.1.357
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular status in young patients with insulin-dependent diabetes mellitus.

Abstract: Early onset of diabetes mellitus is associated with increased left ventricular mass, performance, contractility, and blood pressure. These cardiovascular findings are correlated with increased creatinine clearance and microalbuminuria. These relations suggest that alterations in cardiovascular and renal function may occur in parallel in adolescents with insulin-dependent diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 27 publications
2
26
0
1
Order By: Relevance
“…Contractility was assessed from the correlation between mean velocity of circumferential shortening (corrected for heart rate) and end-systolic wall stress in control subjects. The difference between measured and predicted mean velocity of circumferential shortening for the measured end-systolic wall stress served as an index of contractility (stroke velocity index) [2,9] . Left ventricular mass was calculated with the cube function formula, ASE-cube left ventricular mass=1·04((septal thickness in diastole+left ventricular internal diameter in diastole+left posterior wall thickness in diastole) 3 left ventricular internal diameter in diastole 3 ), that approximates the shape of the left ventricle as a prolate ellipsoid of regular configuration and a ratio of long-to short-axis lengths of 2:1.…”
Section: Echocardiographymentioning
confidence: 99%
See 2 more Smart Citations
“…Contractility was assessed from the correlation between mean velocity of circumferential shortening (corrected for heart rate) and end-systolic wall stress in control subjects. The difference between measured and predicted mean velocity of circumferential shortening for the measured end-systolic wall stress served as an index of contractility (stroke velocity index) [2,9] . Left ventricular mass was calculated with the cube function formula, ASE-cube left ventricular mass=1·04((septal thickness in diastole+left ventricular internal diameter in diastole+left posterior wall thickness in diastole) 3 left ventricular internal diameter in diastole 3 ), that approximates the shape of the left ventricle as a prolate ellipsoid of regular configuration and a ratio of long-to short-axis lengths of 2:1.…”
Section: Echocardiographymentioning
confidence: 99%
“…They suggested that the increased systolic shortening was due to reduced afterload. Kimball et al [2] compared insulindependent diabetes mellitus patients who were a little older (mean age 17·6 years) with controls, and reported increased left ventricular performance measured as stroke volume, cardiac output, fractional shortening, and mean velocity of circumferential shortening, but no significant differences in preload or afterload. These data are in accordance with our data.…”
Section: Increased Left Ventricular Function In Iddm 1737mentioning
confidence: 99%
See 1 more Smart Citation
“…Other changes that are due to glucose induced activation of cPLA2, inhibition of Na + K + ATPase which could be involved in the regulation of vascular permeability, regulation of caldesmone and Another common problem observed in diabetic patients is cardiomyopathy. Up to 25 % of diabetic patients with congestive cardiac failure do not have significant angiographic evidence of coronary vessel disease and there is generally a greater prevalence of congestive heart failure in diabetic compared with non-diabetic patients [6,7]. This has been investigated using a transgenic mouse model which overexpresses PKCb isoform in the heart using a myosin heavy chain promoter to target the transgene to the myocardium.…”
mentioning
confidence: 99%
“…A new theory is postulated suggesting that insulin's activities on the vasculature can be divided into atherogenic and anti-atherogenic actions [7]. The anti-atherogenic actions include vasodilatation and release of nitric oxide (NO), inhibition of tumour necrosis factor (TNF) and angiotensin II actions, amino acid transport and conversion of glucose into glycogen.…”
mentioning
confidence: 99%